Pengaruh Safety Culture Terhadap Implementasi Safety Performance di Perusahaan Bandar Udara - Nico Apriandra Caesariansyah; Adipura Danang Maulana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the influence of safety culture on safety performance at Dewadaru Airport in Karimunjawa. Although several safety aspects have been implemented, issues such as suboptimal infrastructure and weak inter-unit coordination are still present. The research uses a descriptive quantitative approach, with data collected through questionnaires distributed to operational personnel and analysis of task execution logbooks. The data were analyzed using validity and reliability tests, classical assumption tests (normality and heteroscedasticity), and simple linear regression to determine the effect of safety culture on safety performance. The results show that safety culture has a significant influence on safety performance, with a t-value of 6.884, which is greater than the t-table value of 1.679, and a regression coefficient of 0.643. The Adjusted R Square value of 0.497 indicates that safety culture explains 49.7% of the variation in safety performance. These findings are supported by logbook data, which show that safety procedures are consistently followed despite technical challenges. Therefore, strengthening safety culture is essential to continuously improve safety performance.